Uncovering whiteness as discourse: A critical discourse analysis of the in-state resident tuition debate for undocumented students in Texas - Tapia-Fuselier, Nicholas; Jones, Veronica A.; Harbour, Clifford P. (Education Policy Analysis Archives, 2021)
Undocumented college students in the United States encounter a number of structural barriers to postsecondary education success, including disparate in-state resident tuition (ISRT) policies across the country. Texas, the first state to establish ISRT benefits for undocumented college students, has been a site of tension respective to this issue over the last 20 years. In fact, there have been eight legislative attempts to repeal the state’s affirmative ISRT policy. In order to investigate this ongoing ISRT debate in Texas, we used critical discourse analysis methods to analyze the implicit and explicit messages communicated in the policy and surrounding policy discourse. Our conceptual framework, grounded in three constructs of critical whiteness studies including ontological expansiveness, color evasiveness, and individualization, allowed us to uncover whiteness as a pernicious undergirding force within this policy discourse.